Effects of berberine on acquisition and reinstatement of morphine-induced conditioned place preference in mice - Faezeh Vahdati Hassani; Mahmoud Hashemzaei; Edris Akbari; Mohsen Imenshahidi; Hossein Hosseinzadeh (Mashhad University of Medical Sciences, 2016)
Objective: It has been shown that berberine, a major component of Berberis vulgaris extract, modulates the activity of several neurotransmitter systems including dopamine (Da) and N-methyl-D-aspartate (NMDA) contributing to rewarding and reinforcing effects of morphine. Drug craving and relapsing even after a long time of abstinence therapy are the most important problems of addiction. In the present study, we investigated the alleviating effects of berberine on the acquisition and reinstatement of morphine-induced conditioned place preference (CPP) in mice. Materials and Methods: In male NMRI mice, the acquisition of CPP was established by 40 mg/kg of morphine sulphate injection and extinguished after the extinction training and reinstated by a 10 mg/kg injection of morphine.  The effects of different doses of berberine (5, 10, and 20 mg/kg) on the acquisition and reinstatement induced by morphine were evaluated in a conditioned place preference test. Results: The results showed that intraperitoneal administration of berberine (5, 10, and 20 mg/kg) did not induce conditioned appetitive or aversive effects. Injection of berberine (10 and 20 mg/kg) 2 h before the morphine administration reduced acquisition of morphine-induced CPP. In addition, same doses of berberine significantly prevented the reinstatement of morphine-induced CPP. Conclusion: These results suggest that berberine can reduce the acquisition and reinstatement of morphine-induced conditioned place preference and may be useful in treatment of morphine addiction.